Role methodological function of philosophy in scientific knowledge - Сластенко, Е.Ф.; Кадникова, Л.В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
This article addresses the role of philosophical methodology in scientific knowledge.